Strategic integration of social media in IT sector communication: designing effective practices - Kesar, Benu; Joseph, Shaji (Institute of Advanced Engineering and Science, 2025)
This paper explores the transformative role of social media in enhancing communication and workflow efficiency within the information technology (IT) sector. We have introduced the adaptive social media for information technology collaboration (ASMIT) framework. Its goal is to provide a holistic strategy for digital transformation in the IT sector. Employing a mixed method approach, the research combines a systematic literature review with case study of HCL Technologies. Thematic analysis categorizes findings under five core pillars of the ASMIT framework. Results indicate that AI-driven tools, when embedded within collaborative social media platforms, significantly enhance organizational agility, project coordination, and security. The study contributes to IT scholarship by bridging technological integration with human-centered collaboration strategies.